El Saber de la Teoría de la Educación. Su ubicación conceptual - Colom Cañellas, Antoni J. (Teoría de la Educación. Revista Interuniversitaria, 2009)
In this article is established the Theory of Education as a pragmatic theory or theory for practice. Also is distinguished the Theory of Education from Pedagogy and from others theoreticals studys of education. Its areas of application are determinated (formal, no formal and informal) and it is concluded with its own technological applicated caracteritation, common to any under which is pretended to analyses the theoretical question of education.